Molecular Docking Simulation of the antisickling activity of Naringenin-7-O-glucoside and Kaempferol-3-O-glucoside from Uapaca heudelotii Baill. (Phyllanthaceae) and their ADMET profile - Elumba Ekutsu, Grégoire; Mulongo Kitete, Emmanuel; Masengo, Colette Ashande; Gbolo, Benjamin Z.; Iteku, Jeff Bekomo; Mavakala, Bienvenu K.; Mpiana, Pius Tshimankinda; Mudogo, Virima; Ngbolua, Jean-Paul Koto-Te-Nyiwa (Orapuh Journal, 2024)
Introduction Sickle cell disease is a genetic disease that affects the hemoglobin in red blood cells. The symptoms of this public health problem include anemia, painful crises, and an increased risk of infections. In the Democratic Republic of the Congo, the medicinal plant species Uappaca heudelotii, which has been reported to have antisickling activity in vitro constitutes a source of natural antisickling agents for potential clinical applications in sickle cell disease management. Purpose This study aimed to investigate the potential of two secondary metabolites (Naringenin-7-O-glucoside and Kaempferol-3-O-glucoside) from Uappaca heudelotii in treating sickle cell disease by targeting specific receptors (3NFY, 3WCU, 5VTB, and 7EJ1) associated with the condition. Methods Naringenin-7-O-glucoside and Kaempferol-3-O-glucoside from U. heudelotii were evaluated for their interaction with receptors associated with sickle cell disease namely 3NFY, 3WCU, 5VTB, and 7EJ1 using molecular docking simulation. Discovery Studio 2021 (Biovia) software package was used to prepare the receptor, to edit the binding site, and to visualize the results of docking. SWISS ADME and PKCSM bioinformatics tools were utilized for assessing physicochemical parameters and pharmacokinetic properties, respectively. Results Naringenin-7-O-glucoside and Kaempferol-3-O-glucoside exhibited significant interactions with the receptors; Both compounds formed hydrogen bonds with the receptors, indicating strong binding affinity; Naringenin-7-O-glucoside formed 4, 1, 6, and 3 hydrogen bonds with receptors 3NFY, 3WCU, 5VTB, and 7EJ1 respectively; Kaempferol-3-O-glucoside formed 5, 5, 8, and 2 hydrogen bonds with the same receptors respectively, indicating a higher number of interactions. Conclusions The study confirmed the potential of Naringenin-7-O-glucoside and Kaempferol-3-O-glucoside from U. heudelotii as effective agents against sickle cell disease. These compounds demonstrate promising antisickling properties by inhibiting hemoglobin polymerization and the Rapoport-Lübering shunt, rehydrating erythrocytes, and increasing fetal hemoglobin levels.